2006
DOI: 10.1242/jcs.02752
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4-kinase is required for endosomal trafficking and degradation of the EGF receptor

Abstract: The type II alpha isoform of phosphatidylinositol 4-kinase has recently been shown to function in the recruitment of adaptor protein-1 complexes to the trans-Golgi network. Here we show that phosphatidylinositol 4-kinase IIalpha is also a component of highly dynamic membranes of the endosomal system where it colocalises with protein markers of the late endosome and with endocytosed epidermal growth factor. When phosphatidylinositol 4-kinase IIalpha activity was inhibited in vivo using the monoclonal antibody 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 34 publications
11
143
0
Order By: Relevance
“…While in this study PI4K2β depletion did not affect AP-1 recruitment to the TGN (Wang, Wang et al 2003), others showed that PI4K2β can directly interact with AP-1 and regulate AP-1 dependent endosomal sorting of the Wnt receptor Frizzled (Fz) (Wieffer, Cibrian Uhalte et al 2013). At the level of endosomes, PI4K2α and its lipid product PI(4)P localize AP-3 to endosomes to regulates lysosomal cargo delivery (Craige, Salazar et al 2008) and early-to-late endosomal trafficking of ubiquitinated EGFR or Fz (Minogue, Waugh et al 2006;Mossinger, Wieffer et al 2012). Recently, PI4K2α was shown to associate with early endosomal VAMP3 or late endosomal VAMP7.…”
Section: Other Myotubularin Family Members Contribute To Endosomal Pimentioning
confidence: 53%
See 1 more Smart Citation
“…While in this study PI4K2β depletion did not affect AP-1 recruitment to the TGN (Wang, Wang et al 2003), others showed that PI4K2β can directly interact with AP-1 and regulate AP-1 dependent endosomal sorting of the Wnt receptor Frizzled (Fz) (Wieffer, Cibrian Uhalte et al 2013). At the level of endosomes, PI4K2α and its lipid product PI(4)P localize AP-3 to endosomes to regulates lysosomal cargo delivery (Craige, Salazar et al 2008) and early-to-late endosomal trafficking of ubiquitinated EGFR or Fz (Minogue, Waugh et al 2006;Mossinger, Wieffer et al 2012). Recently, PI4K2α was shown to associate with early endosomal VAMP3 or late endosomal VAMP7.…”
Section: Other Myotubularin Family Members Contribute To Endosomal Pimentioning
confidence: 53%
“…A candidate enzyme for PI(4)P synthesis on exocytic vesicles is PI 4-kinase type II α (PI4K2α)a member of the PI4K family previously shown to be associated with endosomes (Minogue, Waugh et al 2006;Mossinger, Wieffer et al 2012), secretory vesicles (Guo, Wenk et al 2003) and the TGN (Wang, Wang et al 2003). PI4K2α was indeed found on MTM1-positive vesicles by immunocytochemistry ( Figure 29) and associated with MTM1 in pull down assay (experiments were done in collaboration with Jocelyn Laporte and Anne-Sophie Nicot, data not shown).…”
Section: Exocytic Vesicles Acquire Pi(4)p Before Plasma Membrane Fusionmentioning
confidence: 99%
“…Kauffmann-Zeh et al (1994) reported that EGF regulates PI4KIIa activity and is associated with ERBB-1 (EGFR), and Minogue et al (2006) showed that PI4KIIa can influence the endosomal trafficking and degradation of EGFR. However, none of these reports show a direct effect of PI4KIIa on kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that PI4KIIa associates with HermanskyPudlak syndrome protein complexes (Salazar et al, 2009). PI4KIIa is necessary for endosomal trafficking and degradation of activated epidermal growth factor receptor (EGFR) (Minogue et al, 2006), and it is also a critical player in the exo-endocytic cycle of synaptic vesicles (Guo et al, 2003). The loss of PI4KIIa in mouse causes late onset degeneration of spinal cord axons (Simons et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Type IIα and IIβ PI4Ks are membrane-bound proteins due to the palmitoylation of a conserved stretch of cysteines in their catalytic domains (24). Immunocytochemical analysis has revealed that they are mostly associated with trans-Golgi, endoplasmic reticulum, and endosomal membranes (25)(26)(27). These type IIα and IIβ enzymes are blocked by adenosine and calcium, but are resistant to wortmannin.…”
mentioning
confidence: 99%